2020
DOI: 10.1037/npe0000129
|View full text |Cite
|
Sign up to set email alerts
|

Economic rationality in youth with emerging mood disorders.

Abstract: Cognitive difficulties are common in persons experiencing anxiety or mood disorders. In this paper we explore the economic concept of rational decision-making in young people with emerging mood disorders by using incentive-compatible experiments involving choices over consumer products. At two time points, separated by six to eight weeks, we measured irrational decision-making (defined as violations of the Generalized Axiom of Revealed Preference) concurrently with levels of anxiety and depression levels using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Our analysis also provides a plausible mechanistic account of the irrationality in the picture task. A severe violation of GARP has been observed in individuals with impaired or less developed cognitive functions (Harbaugh et al, 2001;Camille et al, 2011;Chung et al, 2017) or with a mood disorder (Weinrabe et al, 2020). These findings support the notion that individuals' cognitive limitation or emotional state might contribute to economic irrationality (Kaufman, 1999;Loewenstein, 2000;Pham, 2007;Nitsch and Kalenscher, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…Our analysis also provides a plausible mechanistic account of the irrationality in the picture task. A severe violation of GARP has been observed in individuals with impaired or less developed cognitive functions (Harbaugh et al, 2001;Camille et al, 2011;Chung et al, 2017) or with a mood disorder (Weinrabe et al, 2020). These findings support the notion that individuals' cognitive limitation or emotional state might contribute to economic irrationality (Kaufman, 1999;Loewenstein, 2000;Pham, 2007;Nitsch and Kalenscher, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…This provides evidence of anxiety and biased attentional processes, especially so in major mood disorders (Murphy et al, 1999). A more recent empirical study, evaluating an Australian clinical youth population aged 18-25, found that economic decision-making was significantly impaired for young people suffering from anxiety (Weinrabe et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…As opposed to depression, clinical trait anxiety and its relationship to decisionmaking have not been well researched in the field of behavioural economics with its multidisciplinary capability (Hartley and Phelps, 2012). Overall, only one study (Weinrabe et al, 2020) evaluated youth with emerging mood disorders, with the emphasis on trait anxiety on choice preferences.…”
Section: Discussionmentioning
confidence: 99%